2003
DOI: 10.1007/s00345-002-0301-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and burden of overactive bladder in the United States

Abstract: The National Overactive BLadder Evaluation (NOBLE) Program was initiated to better understand the prevalence and burden of overactive bladder in a broad spectrum of the United States population. Objective: To estimate the prevalence of overactive bladder with and without urge incontinence in the US, assess variation in prevalence by sex and other factors, and measure individual burden. Design: US national telephone survey using a clinically validated interview and a follow-up nested study comparing overactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

64
1,330
20
45

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,970 publications
(1,459 citation statements)
references
References 17 publications
64
1,330
20
45
Order By: Relevance
“…In a rat model of chronic cystitis induced by cyclophosphamide or hydrochloric acid, it has been shown that capsaicin-sensitive bladder afferent neurons increase their excitability due to decreased density of A-type K + (K A ) currents, associated with the decreased expression of the Kv1.4 α-subunit (260,703). Similar somal hyperexcitability due to reduced K A current expression after chronic tissue inflammation has also been detected in afferent neurons innervating the rat stomach (135) or the guinea pig ileum (592). Thus, the reduction in K A current size could be a key mechanism inducing afferent hyperexcitability and pain in visceral organs including the bladder.…”
Section: Disease-induced Changes In Micturitionmentioning
confidence: 57%
“…In a rat model of chronic cystitis induced by cyclophosphamide or hydrochloric acid, it has been shown that capsaicin-sensitive bladder afferent neurons increase their excitability due to decreased density of A-type K + (K A ) currents, associated with the decreased expression of the Kv1.4 α-subunit (260,703). Similar somal hyperexcitability due to reduced K A current expression after chronic tissue inflammation has also been detected in afferent neurons innervating the rat stomach (135) or the guinea pig ileum (592). Thus, the reduction in K A current size could be a key mechanism inducing afferent hyperexcitability and pain in visceral organs including the bladder.…”
Section: Disease-induced Changes In Micturitionmentioning
confidence: 57%
“…Stewart et al [36] performed a CS, population-based, random-sampled study. They collected data from 5,204 Americans by use of a computer-assisted TI method, and reported that the prevalence of OAB was slightly higher in women (16.0% in men, 16.9% in women).…”
Section: Epidemiology Of Oabmentioning
confidence: 99%
“…Health-related quality of life (HRQoL) is profoundly affected in patients who experience OAB symptoms, as demonstrated by clinically meaningful impairments in HRQoL scores [4]. Aspects of life affected by OAB symptoms include sexual health, personal relationships, performing daily activities [5, 6], employment and productivity in the workplace [6, 7].…”
Section: Introductionmentioning
confidence: 99%